Pérola do Maicá: o modo de vida Amazônida como resistência - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
Amazonian biodiversity and sociodiversity open a horizon of immeasurable curiosity, allowing us inexhaustible reflection. This combination of curiosity and such a diverse scenario resulted in an anthropological inquiry to know how Amazonian ways of life resist the onslaughts of hegemonic capitalism. This study seeks to understand these ways of life and how they are constituted as forms of resistance by the residents of the Pérola do Maicá community in the Municipality of Santarém. In order to do so, we went into the daily life of an Amazonian community to understand how these people manage their resistance in their social life and in their bonds with the environment. It is concluded that the relationships between people, the multiplicity of entanglements, create networks of relationships that expand the territorial and existential horizons by means of kinship ties and friendship affections, reinforcing resistance through the exchange and updating of knowledge about the amazon life. In addition, the resistance of the Amazonian peoples is fundamental for the preservation of the environment and for their ways of life in Lake Maicá.
Keywords: Pérola do Maicá; Força Capitalista; Força Amazônida; Lugar; Resistência; CNPQ:: CIÊNCIAS HUMANAS